2013
DOI: 10.1007/s11010-013-1755-y
|View full text |Cite
|
Sign up to set email alerts
|

Relative expressions of miR-205-5p, miR-205-3p, and miR-21 in tissues and serum of non-small cell lung cancer patients

Abstract: Objective was to assess and compare the relative expressions of miR-205-5p, miR-205-3p, and miR-21-3p in tissues and serum among non-small cell lung carcinoma (NSCLC) patients, benign pulmonary conditions patients, and healthy volunteers. Serum samples were obtained between October 2011 and September 2012 from 20 NSCLC patients undergoing surgical treatment, 20 patients diagnosed with a benign lung disease (pulmonary tuberculosis, pneumonia, chronic obstructive pulmonary disease, or interstitial pneumonia) (le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 16 publications
4
52
0
Order By: Relevance
“…Previously, the deregulation of miRs has been reported to be associated with the development and advancement of NSCLC (7,8). Among these miRs, miR-133b has been indicated to inhibit NSCLC growth via targeting epidermal growth factor receptor, suggesting that miR-133b may be a tumor suppressor in NSCLC (9).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the deregulation of miRs has been reported to be associated with the development and advancement of NSCLC (7,8). Among these miRs, miR-133b has been indicated to inhibit NSCLC growth via targeting epidermal growth factor receptor, suggesting that miR-133b may be a tumor suppressor in NSCLC (9).…”
Section: Introductionmentioning
confidence: 99%
“…[17] Hsa-miR-205-3p, which was downregulated to the greatest extent in the present study, was reported to be significantly upregulated in the tissues and serum of non-small cell lung carcinoma (NSCLC) patients compared with the control groups, indicating that miR-205-3p may be a valuable biomarker for diagnosis and prognosis of NSCLC patients. [18] Overall, the modification of miRNA expression profiles may imply the potential roles of miRNAs in the anticancer effects of EGCG on NPC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study used high-throughput microarrays to measure miRNA expression in 122 adenocarcinoma and squamous cell carcinoma (SCC) specimens and demonstrated that the expression of hsa-miR-205 in malignant tissues is an accurate marker of SCC lung cancer (Lebanony et al, 2009). Furthermore, the relative expression of miR-205-5p was significantly higher in non-small cell lung cancer tissues compared with non-cancer adjacent tissues paired specimens (Jiang et al, 2013). Consistent with these observations, our findings displayed an increased miR-205-5p expression in NPC tissues.…”
Section: Discussionmentioning
confidence: 99%